An improved plant leaf protein extraction method for high resolution two-dimensional polyacrylamide gel electrophoresis and comparative proteomics. (February 2013) - Alam, I; Sharmin, SA; Kim, K-H; Kim, Y-G; Lee, JJ; Lee, B-H
Abstract We report here a simple and universally applicable protocol for extracting high quality proteins from plant leaf tissues. The protocol provides improved resolution and reproducibility of two-dimensional polyacrylamide gel electrophoresis (2-DE) and reduces the time required to analyze samples. Partitioning rubisco by polyethylene glycol (PEG) fractionation provides clearer detection of low-abundance proteins. Co-extraction of interfering substances increases the sample conductivity, which results in poor electrophoretic separation. Re-extraction of PEG-fractionated samples with phenol effectively eliminated interfering substances, which results in optimal conductivity during separation in the first dimension of the isoelectric focusing. Smooth focusing reduces analysis time and provides superior resolution in 2-DE gels. Incubating the samples at −80° C instead of −20° C reduced protein precipitation time to 2–3 h. Removal of nonprotein contaminants and the use of sonication increased protein solubility without additional reagents. These changes enabled loading and separation of maximum amounts of proteins, which permitted improved protein identification by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). An immunological approach revealed that little or no ribulose-1, 5-bisphosphte bisphosphate carboxylase oxygenase was present in the PEG supernatant. In addition, low-abundance proteins, such as myelocytomatosis transcription factor (MYC) and alpha subunit of heterotrimeric guanine nucleotide-binding protein complex (Gα), were detected only in the modified PEG supernatant and not in the total protein. These results suggest that our protocol produced high quality proteins and made many low-abundant proteins available for proteomic analysis. The successful application of this protocol for analyzing the leaf proteomes of soybean, Miscanthus sinensis, barley, Chinese cabbage, peanut and tea (Camellia sinensis) suggests that it could be used for comparative proteomic analysis of a wide range of plant leaves.